Paleoenvironmental evolution of the Aptian Romualdo Formation, Araripe Basin, Northeastern Brazil - Bom, Marlone H.H.; Ceolin, Daiane; Kochhann, Karlos G.D.; Krahl, Guilherme; Fauth, Gerson; Bergue, Cristianini T.; Savian, Jairo F.; Strohschoen Junior, Oscar; Simões, Marcello G. [UNESP]; Assine, Mario L. [UNESP] (Elsevier, 2021)
The tectonic evolution of the Equatorial Atlantic Gateway (EAG) throughout the early Cretaceous had global implications. This break-up of western Gondwana has played a significant role in causing, or amplifying, environmental changes due to its influence on ocean chemistry, nutrient distribution, water mass circulation, and bottom waters ventilation. However, the timing of its establishment and the areal extent of this oceanic gateway is still poorly constrained. Marine settings were recorded by the black shales of the Romualdo Formation (Late Aptian), Araripe Basin - Northeastern Brazil, which are known worldwide for their fossil content and importance for paleogeographic reconstructions of Gondwana. In this contribution, we present multiproxy analyses, combining macro- and micropaleontological, as well as sediment compositional data to evaluate paleoenvironmental conditions during the deposition of sedimentary strata assigned to the Romualdo Formation. We investigate the ~100-m-thick succession of the Sobradinho Section, which is the most complete exposure of the Romualdo Formation. Increased abundances of ostracods, the occurrence of agglutinated benthic foraminifera, bakevelliid bivalves, and cassiopid gastropods coincide with levels of relatively high paleosalinity estimates based on the Sr/Ba (strontium/barium) and S/TOC (sulfur/total organic carbon) ratios. These levels correspond to a transgressive system tract and the lower interval of a highstand systems tract. Throughout the section, black shales occur intercalated with sparse sandstone and calcarenite levels, and the deposition of these black shales is associated with dysoxic to anoxic bottom water conditions, as suggested by the V/Cr (vanadium/chrome) ratio. The occurrence of stagnant bottom water conditions may explain the mass mortality of ostracods in the lower interval of the succession. The upper part of the highstand system tract in the studied section was deposited in coastal environments and is characterized by coarser-grained siliciclastic-dominated facies (high log(Zr/Rb) (zirconium/rubidium) ratio), as well as increased phytoclasts and terrigenous (high magnetic susceptibility) contents.
Keywords: Cretaceous; Equatorial Atlantic Gateway; Ostracods; Paleoredox; Paleosalinity